Effect of Impaired Stereoscopic Vision on Large-Scale Resting-State Functional Network Connectivity in Comitant Exotropia Patients - Jin, Han; Chen, Ri-Bo; Zhong, Yu-Lin; Lai, Ping-Hong; Huang, Xin (Frontiers in Neuroscience, 2022)
Abstract Background: Comitant Exotropia (CE) is a common eye movement disorder, characterized by impaired eye movements and stereoscopic vision. Previous studies have shown that CE patients were accompanied by central nervous mechanism changes. However, whether the large-scale brain network changes in CE patients is poorly understood. Purpose: the purpose of this study was to investigate the effect of exotropia and stereoscopic vision dysfunction on large-scale brain network in CE patients using independent component analysis (ICA) method. Methods: Twenty-eight CE patients (mean age, 24.25±1.00 years) and twenty-seven healthy controls (HCs) (mean age, 24.46±1.31years), closely matched for age, sex, and education, underwent resting-state magnetic resonance imaging scans. ICA was applied to extract the resting-state networks (RSNs) in two groups. Then, two-sample t-tests were conducted to investigate different intranetwork FCs within RSNs and interactions among RSNs between two groups. Results: Compared with the HC group, the CE group showed increased intra-network FC in the bilateral postcentral gyrus of the sensorimotor network (SMN), Meanwhile, the CE group showed decreased intra-network FC in the right cerebelum_8 of the cerebellum network (CER), the right superior temporal gyrus of the auditory network (AN) and the right middle occipital gyrus of the visual network (VN). Moreover, FNC(functional network connectivity) analysis showed the CER-AN, SMN-VN, SN-DMN, DMN-VN connections were found to be significantly altered between two groups. Conclusion: Our study highlighted that CE patients had abnormal brain networks related to cerebellum network, sensorimotor network, auditory network and visual network. Our results offer important insights into the neural mechanisms of eye movements and stereo vision dysfunction in CE patients.